Pembelajaran English Basic Structure Melalui Picture Word Inductive Model Berbasis Online Learning Bagi Komunitas Berkebutuhan Khusus (Tuli) - Lailla Tintani Putri; Herlina Yanti; Adipta Wahyu Ferdiansyah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The inability to hear normally makes it difficult for some deaf people to learn English. Meanwhile, English language skills are necessary in globalization. The purpose of this research was to analyze the effect of picture word inductive model (PWIM) toward disabilities of hearing (deaf). The method used was experimental method, which the independent variable was PWIM and the dependent variable was the result of English Basic Structure Learning. The sample was taken by doing direct observation. The research’s result shows that there are significant effect of PWIM application toward student’s English basic structure result especially on disabilities of hearing (deaf) communities.